Some thoughts on the Slavic verbal system (a typological approach) - Kretschmer Anna (Serbian Academy of Sciences and Arts, Institute for the Serbian Language, Belgrade, 2021)
This paper deals with the essential verb categories - the grammatical categories of tense, aspect and mode, as well as with actionality as a lexical and functional category. These categories coexist in the Slavic languages in manifold correlations, determined by the type of language. The paper is focused on tense as the central verb category. In the first part, there is a typological approach to the Slavic verbal system proposed, as a base for its systematic functional description and interpretation. Two prototypes of the verbal system in Slavia can be postulated - a southern and a northern one. The Slavic languages of the Balkan linguistic area (Sprachbund) - Bulgarian and Macedonian - belong to the southern prototype, while the East Slavic languages and Polish belong to the northern prototype. The remaining Slavic languages represent various transitional phases from one prototype to the other. The actual version of the model offered in this paper is synchronically based, but the diachronic approach is considered indispensable for an adequate modelling of the Slavic verbal system. In this context, the paper presents some critical remarks on the modern Slavic grammaticography, with key focus on its methodological and theoretical basis. The last part of the paper presents some approaches to and interpretations of the tense category in some selected recent works.